Whole-genome sequencing of SARS-COV-2 showed wide spread of B.1.525 in February 2021 in Libya. Issue 1 (1st January 2021) - Alhudiri, Inas M.; Ramadan, Ahmad M.; Ibrahim, Khaled M.; Abdalla, Adel; Eljilani, Mouna; Salem, Mohamed Ali; Elgheriani, Hajer Mohamed; El Meshri, Salah Edin; Elzagheid, Adam
ABSTRACT: Alpha (B.1.1.7) SARS-COV-2 variant was detected in September 2020 in minks and humans in Denmark and UK. This variant has several mutations in the spike region (S) which could increase the transmissibility of the virus 43–90% over previously circulating variants. The National Center for Disease Control (NCDC) announced on 24 February 2021 a 25% frequency of B.1.1.7 strain in Libya using a reverse-transcriptase quantitative PCR assay. This assay relies on the specific identification of the H69-V70 deletion in S gene which causes its failure of amplification (SGTF). This deletion is not specific for B.1.1.7, but is also characteristic of two other SARS-COV-2 variants. This study aimed to estimate the frequency of B.1.1.7 and identify other variants circulating in Libya in February 2021. We performed whole genome sequencing of 67 positive SARS-COV-2 samples collected on 25 February 2021 in Libya which were also tested by RT-qPCR for SGTF. Our results showed that 55% of samples had mutations specific to B.1.525 strain and only 3% of samples belonged to B.1.1.7. These findings suggested that B.1.525 was spreading widely in Libya. The use of such RT-qPCR assay, although useful to track some variants, cannot discriminate between variants with H69-V70 deletion. RT-qPCR assays could be multiplexed to identify multiple variants and screen samples prior to sequencing. We emphasize on the need for providing whole-genome sequencing to the main COVID-19 diagnostic laboratories in Libya as well as establishing international collaboration for building capacity and advancing research in this time of the pandemic.